(untitled) (Research, Society and Development, 2022)
Cancer is the main public health problem in the world and is among the four main causes of premature death. Its etiology has a strong association with dietary factors. Based on this information, the production of functional foods has been gaining prominence in the food industry due to the fact that consumers are more aware of the relationship between good nutrition and health, and therefore the demand for foods that, in addition to nourishing, provide benefits, has increased. such as fermented dairy products. The research was carried out in databases such as PubMed, Google Scholar and Scielo, considering articles published in Portuguese, English and Spanish between 2003 and 2022, on the composition and relationship between dairy products and cancer. Fermented dairy products are rich in many highly bioavailable vitamins and minerals and their benefits are associated with the bioactive peptides present in foods. In addition, these products have antioxidant, anticarcinogenic, antimutagenic properties and are excellent matrices for propagation of probiotic bacteria. Given the above, the development of functional dairy foods requires the support of scientific research and must consider consumer expectations, the technological process, appropriate analysis and marketing techniques, and nutritional advantages. More studies are needed to better understand the mechanisms of action and the relationship between dairy products and cancer.